2010
DOI: 10.1039/b913221j
|View full text |Cite
|
Sign up to set email alerts
|

Perfused multiwell plate for 3D liver tissue engineering

Abstract: In vitro models that capture the complexity of in vivo tissue and organ behaviors in a scalable and easy-to-use format are desirable for drug discovery. To address this, we have developed a bioreactor that fosters maintenance of 3D tissue cultures under constant perfusion and we have integrated multiple bioreactors into an array in a multiwell plate format. All bioreactors are fluidically isolated from each other. Each bioreactor in the array contains a scaffold that supports formation of hundreds of 3D micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
389
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 398 publications
(396 citation statements)
references
References 32 publications
6
389
0
1
Order By: Relevance
“…Our data are consistent with another study showing that 3-dimensional cultures under constant perfusion can maintain the hepatocytes function. 20 Our data also demonstrated that DSM provide comparable environment for hepatocytes survive and function with DLM, since they had the similar mechanism.…”
Section: Discussionsupporting
confidence: 51%
“…Our data are consistent with another study showing that 3-dimensional cultures under constant perfusion can maintain the hepatocytes function. 20 Our data also demonstrated that DSM provide comparable environment for hepatocytes survive and function with DLM, since they had the similar mechanism.…”
Section: Discussionsupporting
confidence: 51%
“…Linda Griffith, a bioengineer at MIT, has built silicon scaffolds less than 2 centimetres across and filled them with wells that allow liver cells to grow in three dimensions 7 . These structures are placed inside multiwell plates.…”
Section: The Real Mccoymentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37][38] Several strategies have previously been proposed to culture LSECs while retaining their phenotype. [37][38][39][40][41][42][43] LSECs, cultured in media supplemented with lipids and oleic acid, in particular, was shown to maintain their metabolic and endocytotic activity for up to 5 days by influencing Akt/PKB and ERK signaling pathways. 39 Another study with culturing LSECs and hepatocytes in a three-dimensional (3D) microreactor shows retention of LSEC phenotype expression for 13 days, primarily through modulation of vascular endothelial growth factor in the culture media.…”
mentioning
confidence: 99%